Kekuatan Hukum Perjanjian Pengikatan Jual Beli Tanah Dibuat Dibawah Tangan - Adriansa, Muhammad Zaky; Dewi, Iga Gangga Santi; Priyono, Ery Agus Agus (Fakultas Hukum Universitas Bangka Belitung, 2022)
This research discusses the legal force of binding sale and purchase agreements under the hands made by the parties without witnesses and only waarmarking by a notary. The research method used is the analytical descriptive method, a research method that reveals problems, analyzes a problem, examines, and interprets it into conclusions and suggestions in a systematic way so that it is easy to understand. Normative Juridical approach method, namely legal research that uses secondary data sources such as principles the doctrines in the science of law. The results of the study can be concluded that the underhand Sale and Purchase Agreement (PPJB) is a form of agreement between two parties who agree to bind themselves, which is made jointly. Even though PPJB under the hand can be made freely by the parties who want to make an agreement, it may not violate the provisions of Article 1320 of the KUHPerdata. PPJB made before an authorized official and PPJB made privately have the same legal force. PPJB under the hand made by the parties without witnesses and only waarmarking by a notary, the strength of proof is only between the parties. If the parties do not deny and acknowledge the signature in the agreement, then the PPJB under the hand has perfect power as an authentic deed.